Impairments of interpersonal functioning: empathy and intimacy in borderline personality disorder - Jeung, Haang; Herpertz, Sabine (Psychopathology, 2014)
Impairments of interpersonal functioning are central to borderline personality disorder (BPD). Patients with BPD suffer from severe psychosocial dysfunction in general and - among others - disturbed romantic relationships. Compounding the problem, the diagnosis of BPD interferes with therapeutic relationships and results in pejorative and discriminatory clinical practices. Previously, interpersonal dysfunction has been related to emotional dysregulation, behavioral dyscontrol, and impaired social cognition. However, these features may be intertwined yet separate. In this review, we will focus on disturbed empathy and intimacy as they are referred to as two discrete impairments of interpersonal functioning in the new DSM-5 Section III. The aim of this review is to contribute to a comprehensive, integral understanding of interpersonal dysfunction in BPD based on the behavioral and neurobiological studies available up to now. Despite some inconsistencies, behavioral studies in BPD patients indicate impaired cognitive and affective empathy particularly in complex and ecologically valid measurements. These findings are reflected even more consistently in functional magnet resonance imaging studies. Low quality of intimate relationships in BPD may at least partially result from lower mentalizing abilities and cognitive empathy, higher personal distress and affective empathy in the social context. Finally, the evaluation of the severity and quality of impairment of interpersonal functioning may enable clinicians and researchers to describe and to understand the mechanisms of interpersonal dysfunction better, and to improve the effectiveness of the treatment of patients with BPD.
Gesehen am 29.09.2020